Diagnosis and treatment of paragangliomas and pheochromocytomas: a survey from the Italian Association for Neuroendocrine Tumors - Pietroluongo, Erica; Marretta, Antonella Lucia; Cives, Mauro; Andrini, Elisa; Della Sala, Leonardo; Dell’Unto, Elisabetta; Carli, Alice; Mikovic, Nevena; Mascagni, Ilaria; Panzuto, Francesco; Tafuto, Salvatore (Frontiers in Endocrinology, 2025)
BackgroundPheochromocytomas (PCCs) and paragangliomas (PPGLs) are rare neuroendocrine neoplasms (NENs) with heterogeneous clinical presentations. Given the rarity of PCCs/PPGLs and the paucity of high-level evidence, therapeutic decisions and treatment sequences vary across institutions. This survey explored current diagnostic practices and treatment patterns among Italian healthcare professionals (HCPs) dedicated to NENs.MethodsAn online survey was conducted among Italian HCPs, members of the Italian Association for Neuroendocrine Tumors (ITANET). The survey included 33 questions covering diagnosis, genetic counseling, imaging, and treatment approaches. Responses were collected from December 15, 2023, to May 30, 2024, and analyzed using descriptive statistics to identify trends in clinical practice.ResultsWe recorded 80/355 responses from invited HCPs (response rate: 23%). Most HCPs (90%) referred all PCC/PPGL patients for genetic counseling, with 71% adopting gene panels for syndromes like VHL, MEN2, and familial PPGLs. Functional imaging preferences included 68Ga-DOTA-peptide PET/CT (38%), 18F-DOPA PET/CT (26%), and 123I-MIBG scintigraphy (19%). First-line systemic treatments favored somatostatin analogs (39%), clinical trial enrollment (19%), and CVD chemotherapy (15%). Radioligand therapy (RLT) emerged as the preferred second-line treatment (49%). Overall, RLT was perceived as the most effective treatment for achieving objective responses, durable responses, and improving health-related quality of life.ConclusionsClinical wisdom rather than formal evidence and guidelines recommendations appears to guide the management of PCC/PPGLs among Italian HCPs. International, multi-institutional clinical trials designed to take into account the rarity of PCCs/PPGLs are needed to generate high-level evidence and provide guidance for standard clinical practice.